2018
DOI: 10.1111/gbb.12472
|View full text |Cite
|
Sign up to set email alerts
|

Predicting loneliness with polygenic scores of social, psychological and psychiatric traits

Abstract: Loneliness is a heritable trait that accompanies multiple disorders. The association between loneliness and mental health indices may partly be due to inherited biological factors. We constructed polygenic scores for 27 traits related to behavior, cognition and mental health and tested their prediction for self-reported loneliness in a population-based sample of 8798 Dutch individuals. Polygenic scores for major depressive disorder (MDD), schizophrenia and bipolar disorder were significantly associated with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 96 publications
4
24
0
1
Order By: Relevance
“…Contrary to the phenotypic associations, few studies have investigated the genetic associations between well-being and well-being related traits. A genetic investigation of loneliness (Abdellaoui et al 2018 ) revealed a strong negative association between a polygenic score for loneliness and subjective well-being, and a positive association with neuroticism and depression, indicating genetic links between the 3-WBS and loneliness. With regard to self-rated health, twin studies have demonstrated that both genes and the environment contribute to the association with well-being (Roysamb et al 2003 ), but to our knowledge no molecular genetic study has been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the phenotypic associations, few studies have investigated the genetic associations between well-being and well-being related traits. A genetic investigation of loneliness (Abdellaoui et al 2018 ) revealed a strong negative association between a polygenic score for loneliness and subjective well-being, and a positive association with neuroticism and depression, indicating genetic links between the 3-WBS and loneliness. With regard to self-rated health, twin studies have demonstrated that both genes and the environment contribute to the association with well-being (Roysamb et al 2003 ), but to our knowledge no molecular genetic study has been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Over 34 out of the 60 traits in the genetic correlation analyses showed a significant genetic association with loneliness, suggesting widespread shared genetic influences (e.g., pleiotropic effects) or causal relationships between loneliness and several traits. MDD has been strongly associated with loneliness in previous studies [52][53][54] , but evidence from longitudinal studies indicates that loneliness and depression are conceptually and statistically different constructs. [53][54][55] Our results confirm the strong biological ties between loneliness, major depression, and depressive symptoms in both research ascertained samples and EHR from a hospital population.…”
Section: Discussionmentioning
confidence: 89%
“…These findings complement several lines of evidence. First, previous studies report the strongest correlations between loneliness and neuroticism or extraversion (Atak, 2009; Teppers et al, 2013; Mund and Neyer, 2016), although several studies also identify correlations of loneliness with openness, agreeableness and conscientiousness (Lopes et al, 2003; Abdellaoui et al, 2018b). Second, loneliness and neuroticism exhibited a considerable genetic overlap measured by both genetic variants and familial relationships (Abdellaoui et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%